Influence of pumpkin seed cake and extruded linseed on milk production and milk fatty acid profile in Alpine goats. (3rd April 2017) - Klir, Z.; Castro-Montoya, J. M.; Novoselec, J.; Molkentin, J.; Domacinovic, M.; Mioc, B.; Dickhoefer, U.; Antunovic, Z.
Abstract : The aim was to determine the effect of substituting pumpkin seed cake (PSC) or extruded linseed (ELS) for soya bean meal in goats' diets on milk yield, milk composition and fatty acids profile of milk fat. In total, 28 dairy goats were divided into three groups. They were fed with concentrate mixtures containing soya bean meal (Control; n =9), ELS ( n =10) or PSC ( n =9) as main protein sources in the trial lasting 75 days. Addition of ELS or PSC did not influence milk yield and milk gross composition in contrast to fatty acid profile compared with Control. Supplementation of ELS resulted in greater branched-chain fatty acids (BCFA) and total n-3 fatty acids compared with Control and PSC ( P <0.05). Total n-3 fatty acids were accompanied by increased α -linolenic acid (ALA, C18:3n-3; 0.56 g/100 g fatty acids) and EPA (C20:5n-3; 0.12 g/100 g fatty acids) proportions in milk of the ELS group. In contrast, ELS and PSC resulted in lower linoleic acid (LA, C18:2n-6; 2.10 and 2.28 g/100 g fatty acids, respectively) proportions compared with Control (2.80 g/100 g fatty acids; P <0.05). Abovementioned resulted in lower LA/ALA ratio (3.81 v . 7.44 or 6.92, respectively; P <0.05) with supplementation of ELS compared with Control or PSC. The PSC diet decreased total n-6 fatty acids compared with the Control (2.96 v . 3.54 g/100 g fatty acids, P <0.05). Oleic acid ( c 9-C18:1), CLA ( c 9, t 11-18:2) and t 10-, t 11-C18:1 did not differ between treatments ( P ⩾0.08), although stearic acid (C18:0) increased in ELS diets compared with Control (12.7 v . 10.2 g/100 g fatty acids, P <0.05). Partially substituted soya bean meal with ELS in hay-based diets may increase beneficial n-3 fatty acids and BCFA accompanied by lowering LA/ALA ratio and increased C18:0. Pumpkin seed cake completely substituted soya bean meal in the diet of dairy goats without any decrease in milk production or sharp changes in fatty acid profile that may have a commercial or a human health relevancy.